Determinant of adherence with health protocols of COVID-19 among market traders - Amelia, Novita Ridha; Permatasari, Tria Astika Endah (Intelektual Pustaka Media Utama, 2024)
Amid the COVID-19 pandemic, extensive restrictions were imposed on public facilities, including markets. Market traders and visitors were required to adhere with the health protocols government-established. This study's objective is to identify the factors influencing adherence with health protocols among traders. A cross-sectional survey was carried out in traditional and modern market located in Bogor Regency, Indonesia, from March to June 2022. The study encompassed all registered traders belonging to the traditional and modern market association. A total of 240 traders were chosen through a systematic random sampling method based on a hypothesis 2 test of population proportion. Primary data was gathered using a questionnaire and the research data were analyzed using binary logistic regression. In traditional markets, the majority of traders, about 65.0%, did not adhere with the health protocols, whereas in modern markets, approximately 71.7% of traders adhered to the protocols. The determinants of adherence to health protocols were knowledge (p=0.007; OR=3.311; 95% CI=1.395-7.857) in traditional markets and perceived susceptibility (p=0.001; OR=10.377; 95% CI=2.494-43.180) in modern markets. Knowledge and perceived susceptibility are determinant of market traders' adherence with health protocols. Enhanced adherence to health protocols can be achieved by boosting traders' understanding and awareness of COVID-19.